Concordance and complementarity in Intellectual Property instruments - Marco Grazzi; Chiara Piccardo; Cecilia Vergari (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2019)
This work investigates the relationship between proxies of innovation activities, such as patents and trademarks, and firm performance in terms of revenues and growth. By resorting to the virtual universe of Italian manufacturing firms we provide a rather complete picture of the innovation activities of Italian firms, in terms of patents and trademarks, and we study whether the two instruments for protecting Intellectual Property (IP) exhibit complementarity or substitutability. In addition, and to our knowledge novel, we propose a measure of concordance (or proximity) between the patents and trademarks owned by the same firm and we then investigate whether such concordance appears to exert any effect on performance.
Keywords: O31; O34; L25; 330; Trademarks; Patents; Innovation; Intellectual Property; Complemen-tarity; Concordance; Technological proximity; firm performance; firm growth